High platelet counts increase metastatic risk in huge hepatocellular carcinoma undergoing transarterial chemoembolization. Issue 10 (10th March 2016) - Xue, Tong‐Chun; Ge, Ning‐Ling; Xu, Xin; Le, Fan; Zhang, Bo‐Heng; Wang, Yan‐Hong
Abstract : Aim: Accumulating evidence suggests platelets play critical roles in tumor metastasis. Moreover, the role of platelets in metastasis is partially correlated with inflammation. However, evidence regarding the contribution of platelets to hepatocellular carcinoma (HCC) metastasis is lacking. This study investigated the association between platelets and metastatic risk in HCC. Methods: We used huge HCC (diameter over 10 cm), a tumor subgroup with a strong inflammatory background, as a model to evaluate the potential predictive role of platelets and platelet‐related biomarkers for metastasis in HCC patients undergoing transarterial chemoembolization. A logistic regression model was used to analyze risk factors for metastasis. Results: Patients with huge HCC ( n  = 178) were enrolled, and 24.7% (44/178) of patients had remote metastases after treatment. Univariate analyses showed high platelet counts ( P =  0.012), pretreatment platelet‐to‐lymphocyte ratios (pre‐PLR) of 100 or more ( P =  0.018) and post‐PLR of 100 or more ( P =  0.013) were potential risk factors for metastasis. Furthermore, multivariate analyses showed high platelet counts (odds ratio, 2.18; 95% confidence interval, 1.074–4.443; P =  0.031) and platelet‐related biomarkers were independent risk factors for HCC metastasis. Particularly, the risk of metastasis in patients with high post‐PLR values was significantly greater than patients with low post‐PLR values. For tumor response and survival, patients with high platelet counts had faster disease progression ( P =  0.002) and worse survival ( P <  0.0001). Conclusion: High platelet counts increase the extrahepatic metastasis risk of huge HCC undergoing chemoembolization, which supply clinical verification of the association between high platelet counts and HCC metastasis.